Implications of Interfacial Energetics on the Tack/Debonding of Single and Hybrid Pressure Sensitive Adhesives (International Journal of Scientific Research and Management (IJSRM), 2021)
This paper present the implications of interfacial energetics on the tack/debonding of pressure-sensitive adhesives (PSA). The materials used include acrylic, pvc-abro, polyurethane and epoxy by single and hybrid combinations. Mild steel plate of 130mm x 130mm with 1.2mm thickness was used as a substrate. The contact angle was measured on surfaces of PSA and the substrate using OWK and Wu models. The force required to debond the PSA from the substrate (the tack) was measured with a universal testing machine. The results gave the maximum deflections as 4.9074 x10-4 N/mm2 and tack as 3.35769 x10-5 N/m for single PSA of Epoxy are higher than those for Acrylic, Pvc-Abro and Polyurethane PSAs materials. However, with Acrylic/Epoxy and Epoxy/ Pvc Abro hybrids, higher tack forces of 3 x10-5 mJ and 2.725 x 10-5mJ with corresponding higher values of 2.28225 x10-4N/mm2 and 1.61243 x10-4N/mm2 maximum deflections were obtained. These results showed that epoxy is better from tack force. The results clearly show that all the properties – surface free energy, work of adhesion, and tack are higher for hybrid PSA than for the single PSAs ranging from 1.5% to up to 80% difference. It was observed that as the angle of contact increased, the work of adhesion and cohesion increased. The results of this work can find application in dentistry in dentin/adhesive interface and hybridization of dental hard tissues with modified adhesive systems. Applications can also be found in carpentry, in polymer composites for automobile bodies and ceramics.